Report from the PHING Special Interest Group Meeting 14th EAHIL Conference. 11-13 June 2014, Rome (Journal of EAHIL, 2017)
The Pharmaceutical Information Group (PHING) met on the Wednesday during the EAHIL Conference 2014.Comprising 10 delegates from 4 countries, the meeting was led by Co-Chairs Francesca Gualtieri from Rottapharm(Italy) and Michelle Wake from the UCL School of Pharmacy (UK).